Ação interativa e orientação do auto-exame das mamas durante a consulta ginecológica de enfermagem - Linard, Andréa Gomes (2005)
Severa! causes threaten womens well-being, unlcashed by socio-cultural, technological, professional and family events influencing ou the appearance of several types of câncer and similar diseases, with high inortality rates. Through an interactive action with the Client, the nurse can influence significantly on the reduction of these rates, encouraging changes in their behavior, in particular, the adoption of the monthly habit of the Breast Seif-Exam (BSE). We proposed to work based on the thesis that the interactive action established between nurse-clicnt can favor and make possible the persuasive communication, its validation and the transmission ofinformation, aiming to raise on the client the intcrcst in leaming and the wiil to solve doubts. We aimed to identify the factors that influence the interactive action between nurse-patient; describe the way it is being proccsscd, in the nurse practice, the interactive action between nurse-client, and present based on Travelbee’s Theory (1979) a paradigm of implementation of the interactive rclationship nurse-clicnt. This study has a qualitative approach, and it was conducted at Instituto de Prevenção do Câncer do Ceará (ll’CC) during the months of May, June and July, 2004. Data were colleeted during the Interactive Rclationships (IRs) nurses-clients, in the gynecological nursing consultations. lhe instrument of data collection used was the participative observation with the help of a field diary and a tape recordcr, according to authorization obtained. The nurses, subjects of this study were nicknatned as Selene, Melanipe, Eleutera, Cnssa and Electra. We followed tive different moments in the interactive relationship (IR) of each of the fíve nurses. For tlie organization and analysis of data we used the analysis of content method, Bardin (1977), Rodrigues and Leopardi (1999). The content of the dialogues suggested fíve categories, being them: the communication as incentive to the habit ofthe Breast Self-Exam; onentation of the nurse direeted to the success of the communication between doctor and patient; care and technology in the Breast Self-Exam; presence ofrisk factors to the breast câncer and the verbal , Melanipe, Eleutera, Cnssa and Electra. We followed tive different moments in the interactive relationship (IR) of each of the fíve nurses. For tlie organization and analysis of data we used the analysis of content method, Bardin (1977), Rodrigues and Leopardi (1999). The content of the dialogues suggested fíve categories, being them: the communication as incentive to the habit ofthe Breast Self-Exam; onentation of the nurse direeted to the success of the communication between doctor and patient; care and technology in the Breast Self-Exam; presence ofrisk factors to the breast câncer and the verbal communication ofthe nurse in the consultation. The results show that the interactive action nurse-client is, in the majority, prevailed by a mechanical and repetitive communication, being emphasizcd stereotypical orientations, not prioritizing the feedback of the information provided to the clients referring to the adoption of the monthly habit of the BSE and that the techniques of expression, clarifícation and validation of information are not emphasized, during the communication. It is necessary a documentary and more effective collaboration of public health policies and of social promotion, conccming the number of clients to be attended by each professional.